Supporting mental health of medical students: Needs and demands concerning an e-mental health application within medical education - Grüneberg, Catharina; Bäuerle, Alexander; Karanukaran, Sophia; Darici, Dogus; Jansen, Christoph; Dörrie, Nora; Benson, Sven; Teufel, Martin; Robitzsch, Anita (GMS Journal for Medical Education)
Background: Digital technologies are increasingly integrated into medical education and healthcare services. Studies have demonstrated the efficacy of e-mental health approaches, offering cost-effective, user-friendly, anonymous, and geographically flexible support. Objective: This study aims to investigate the needs and demands of medical students regarding the design of an e-mental health application within the context of medical education to foster stress management and personal skills. Methods: A cross-sectional study was conducted from November 2022 to July 2023 at the University of Duisburg-Essen, Germany. N=229 students were incorporated in the final data evaluation. The survey comprised standardized and established self-generated inquiries. Needs and demands were analyzed descriptively. A cluster analysis was conducted to explore hypothetical subgroups. Differences and similarities of the clusters were compared. Results: Most students expressed a preference for smartphone or tablet accessibility, with sessions lasting between 10 to 20 minutes during stressful situations and on an as-needed basis. Participants indicated a desire for information and practical exercises related to self- and time-management, self-esteem and confidence, coping with helplessness, learning methodologies, and self-care/resilience. Video, downloadable, and audio content along with access to expert guidance, were deemed valuable. K-medoids clustering revealed a low and high burden cluster. Conclusions: By aligning with specific needs and demands of target populations, e-mental health apps with enhanced usability and a more user-focused approach can be developed to establish a blueprint for an e-mental health app tailored to their requirements.